The trend of suicide and self-harm in the Chinese population from 2018 to 2022 based on ambulance medical emergency cases: a retrospective study - Ruizhe Yang; Jinsu Zhou; Francis Manyori Bigambo; Wu Yan; Xu Wang; Haibo Yang (Frontiers in Public Health)
ObjectiveThis study investigates the trends of suicide and self-harm in Nanjing, China, through 4 years of data collection, aiming to provide valuable information for developing effective suicide prevention strategies.MethodsThis descriptive study analyzed Nanjing Emergency Medical Center (NEMC) ambulance records from Nanjing (2018–2022) to investigate suicide and self-harm events. Out of 689,305 records, 4,261 cases were included after exclusions. The study categorized incidents into 4,103 suicide events and 158 self-harm cases. Descriptive statistics and content analysis were conducted to identify characteristics and themes related to these events, with age groups defined according to American Medical Association standards.ResultsThe study highlights drug poisoning as the leading method, accounting for 63.56% of the 4,103 suicide events. It notes significant trends by age, gender, and season, with males showing higher rates of self-harm. The study emphasizes the need for targeted prevention strategies, particularly focusing on drug-related suicides among adults and adolescents, as well as the prevalence of various self-harming behaviors.ConclusionTo reduce self-harm and suicide, interventions must be strengthened for women, who experience higher rates. Key strategies include regulating pesticides and psychotropic drugs, increasing access to mental health resources, and launching community awareness campaigns. Additionally, training healthcare providers and promoting family education can enhance support for women facing mental health challenges.